Hiperpotasemia refractaria: su fisiopatología y tratamiento - Carlos Guido Musso; Jerónimo Aguilera Diaz; Manuel Vilas; María Badolato; Alberto Bonetto; Daniel Luna; Luis Algranati; Ricardo Jauregui (Revista del Hospital Italiano de Buenos Aires)
-